Some Quinoline, Quinazoline and Pyrazine Derivatives as Antitubercular-Antibacterial Agents - Desai, Pratibha; Naik, Jiten; Desai, C.M.; Patel, Dinesh (Asian Journal of Chemistry, 2010)
Antitubercular/antibacterial testing have been reported keeping in mind different types of structures of compounds, such as benzene nucleus linked to quinoline, pyrazine to quinazoiine and nicotine to quinazoline.